IMPLEMENTATION OF CHARACTER EDUCATION DISCIPLINE AND RESPONSIBILITY OF 6th GRADE STUDENTS AT SDN BANYUAJUH 6 - Bella Maulidiawati; Agung Setyawan; Mohammad Usman; Moh Rahbini (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This study aims to identify and describe the application of character education to discipline and responsibility of students at SDN Banyuajuh 6, as well as to identify students' behavior in applying the character of discipline and responsibility. This type of research is a quantitative descriptive research with a survey method. The sampling technique used a proportional stratified cluster random sampling technique. Data collection techniques used in the form of interviews, questionnaires (questionnaire), and observation. Data were analyzed using quantitative descriptive statistics. The results of the study showed that the application of character discipline and student responsibility education at SDN Banyuaju 6 was carried out in a good proportion (96.5%). The results of the study show that the application of character education is integrated with self-development programs including spontaneous activities, routine activities, conditioning, and exemplary, integrated into the learning process, and school culture. the behavior of students who have applied the character of discipline in the moderate category (53.6%), as many as 15 students. On the other hand, student behavior in applying the character of responsibility is in the good percentage category (78.6%). Based on the research results, it is better if this character education is carried out in a sustainable manner and to improve one's own character. Another way is to give examples, appreciation, literacy activities, share inspirational experiences and so on